Association of time to antibiotics and clinical outcomes in adult hematologic malignancy patients with febrile neutropenia. (June 2017) - Butts, Allison R; Bachmeier, Christina Carracedo; Dressler, Emily V; Liu, Meng; Cowden, Ann; Talbert, Jeff; Adams, Val R
Objective: The objective of this study was to determine the clinical impact of time to antibiotic administration in adult inpatients who have hematologic malignancies and develop febrile neutropenia. Methods: A retrospective chart review was conducted to screen for all febrile neutropenia events amongst adult hematologic malignancy patients between 1 January 2010 and 1 September 2014. All included patients were admitted to the hospital at the time of fever onset, having been admitted for a diagnosis other than febrile neutropenia. Descriptive statistics and logistic generalized estimated equations were used to analyze the data. Results: Two hundred forty-four neutropenic fever events met inclusion criteria. Thirty-five events (14.34%) led to negative clinical outcomes (in-hospital mortality, intensive care unit transfer, or vasopressor requirement), with an in-house mortality rate of 7.4%. The time to antibiotics ranged from 10 min to 1495 min. The median time to antibiotics in the events that led to negative outcomes was 120 min compared to 102 min in the events that did not lead to the negative outcome ( p = 0.93). Conditional order sets were used to order empiric antibiotics in 176 events (72.1%) and significantly reduced time to antibiotics from 287 min to 143 min ( p = 0.0019). Conclusion: Prolonged time to antibiotic administration in hematologic malignancy patients who develop neutropenic fever was not shown to be associated with negative clinical outcomes.